2013
DOI: 10.1111/medu.12105
|View full text |Cite
|
Sign up to set email alerts
|

Research on problem‐based learning: future challenges

Abstract: discourse about current thinking and future approaches and challenges to research in, and application of, problem-based learning (PBL) in the learning environment. Diana Dolmans:Many claims are made for problem-based learning (PBL), which has been implemented worldwide across many schools. But what are these claims and what evidence is available so far? Does PBL enhance domain-specific knowledge acquisition? Does PBL enhance the application and transfer of domain-specific knowledge? Does PBL enhance the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 21 publications
0
37
0
2
Order By: Relevance
“…It is known that students' perceptions of their study context influence their study behaviors in general (Biggs, 2003) and in PBL (Duke, Forbes, Hunter, & Prosser, 1998;Ellis, Goodyear, Brillant, & Prosser, 2008) and not necessarily in desirable ways (Dolmans & Gijbels, 2013;Winning et al, 2012). Such relational study behaviors among groups have also been demonstrated and referred to as avoider or engager groups, with avoider groups adopting approaches in avoiding group engagement similar to those used by the Australian groups in our study (Yan & Kember, 2004).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is known that students' perceptions of their study context influence their study behaviors in general (Biggs, 2003) and in PBL (Duke, Forbes, Hunter, & Prosser, 1998;Ellis, Goodyear, Brillant, & Prosser, 2008) and not necessarily in desirable ways (Dolmans & Gijbels, 2013;Winning et al, 2012). Such relational study behaviors among groups have also been demonstrated and referred to as avoider or engager groups, with avoider groups adopting approaches in avoiding group engagement similar to those used by the Australian groups in our study (Yan & Kember, 2004).…”
Section: Discussionmentioning
confidence: 84%
“…So that student groups can engage fully with the PBL process in health professional education from the commencement of their study program, care must be taken to ensure that curriculum design and assessment are constructively aligned with PBL goals (Biggs, 2003;Dolmans & Gijbels, 2013). Educators also need to address students' understandings of knowledge and learning.…”
Section: Discussionmentioning
confidence: 99%
“…In particular PBL has gained huge interest in the 1980s onward, due to the developmental work done by its founder Howard Barrows from McMaster University in Canada and from Maastricht University in the Netherlands, which institution derived its entire identity to a large part from problem-based learning. Despite significant research efforts to establish the superiority of PBL curricula, the general outcomes have been somewhat less than expected (Dolmans and Gijbels 2013). However, many studies on a more detailed level have shown that components of PBL are effective.…”
Section: Indications For the Effectiveness Of The Cbcr Methodsmentioning
confidence: 95%
“…This study focused on the "kind of student" variables suggested by Dolmans and Gijbels (2013). Entering medical students are expected to be capable of empathy and self-reflection and to develop those abilities further during their education and practice.…”
mentioning
confidence: 99%